Improving Antigenicity of the Recombinant Hepatitis C Virus Core Protein via Random Mutagenesis. (29th August 2011) - Huang, Chen-Ji; Peng, Hwei-Ling; Cheng, Chih-Yu
Abstract : In order to enhance the sensitivity of diagnosis, a recombinant clone containing domain I of HCV core (amino acid residues 1 to 123) was subjected to random mutagenesis. Five mutants with higher sensitivity were obtained by colony screening of 616 mutants using reverse ELISA. Sequence analysis of these mutants revealed alterations focusing on W 84, P 95, P 110, or V 129 . The inclusion bodies of these recombinant proteins overexpressed in E. coli BL21(DE3) were subsequently dissolved using 6 M urea and then refolded by stepwise dialysis. Compared to the unfolded wild-type antigen, the refolded M3b antigen (W 84 S, P 110 S and V 129 L) exhibited an increase of 66% antigenicity with binding capacity of 0.96 and affinity of 113 μ M −1 . Moreover, the 33% decrease of the production demand suggests that M3b is a potential substitute for anti-HCV antibody detection.